Design and Development of a Mobile Application for the Control and Prevention of Viral Gastroenteritis as a Public Health Problem - Zandi, Milad; Alizadeh, Ismaeil; Soltani, Saber; Vali, Mohebat; Ebrahimi, Saeedeh; Abbasi, Samaneh (Journal of Liaquat University of Medical & Health Sciences, 2022)
Objective: This study aims to design and implement a mobile application, "Viral Gastroenteritis", and assess mobile users' satisfaction with this application. Methodology: This study was conducted in February 2021 in two stages: designing and constructing a viral gastroenteritis disease application based on the Android system and investigating mobile users' satisfaction with this application. Results: Six hundred individuals responded to the questionnaire in this study; 36.5 % were males, 63.5 % were females, 35% were between 20-30 years old, and 43.83% had a bachelor's degree. The study results showed that more than 95% and 90% of the participants had no trouble installing the app. The images adequately conveyed the meaning of viral gastroenteritis, respectively. Conclusion: According to the inquiry outcomes, this didactic software can increase users' awareness when facing viral gastroenteritis. Keywords: Viral gastroenteritis, Public health, Mobile application, Software, Rotavirus, Norovirus.